Study on the Tensile Strength and Crack Development of Granite Crystal Models with Different Fabrics. (20th May 2021) - Du, Guangsheng; Chen, Shijiang; Li, Zhihao
Abstract : According to the relationship between the development of hydraulic fracture and the distribution of different rock and mineral fabrics, digital image technology was used in this study based on the discrete element particle flow method. An SCGM numerical model, which can control fabric and refine mesoscopic crystal defects, was constructed. The tensile strength test of granite specimens with different component contents and polymerization conditions was conducted, with the monitorization of damaged cracks. The test results showed that (1) the SCGM model could construct a model of a crystal structure containing variable components and polymerization, to achieve numerical experiments of different parameters; (2) compared with previous models, the SCGM model can reflect internal stress change of a specimen with the variation of the structure. At the same time, the contained crystal structure can characterize different failure modes such as intergranular cracks of different components, grain boundary cracks of the same component, and transgranular cracks, which were in good agreement with the actual failure state of granite; (3) the mica content of the specimen and its strength presented a linear relationship of y = − 14.723 x + 12.642 . The degree of polymerization of the components and the strength of the specimens were both affected by the accumulation of microcracks and stress concentration, which appeared to increase first and then decrease. When the specimen was broken, the number of microcracks and the degree of polymerization of the components also increased first and then decreased. The SCGM model can construct a numerical model of granite with arbitrary fabric and crystal structure and provide a hydraulic fracturing analysis method.